Early Day Cattle Drives - Jim Hoy (Symphony in the Flint Hills, 2011)
The big Texas-to-Kansas trail drives in the openrange era that followed the Civil War gave birth to the cowboy and helped to establish Kansas as one of the premier cattle-raising states in the nation. From 1866 to 1885, over six million longhorns made their way north.
Keywords: Longhorns; Civil War; cowboy; cattle; Texas; Flint Hills; Fort Worth; Dallas; Baxter Springs; Edward Piper; Kansas City; Sedalia; St. Louis; Cottonwood Falls; Elisha Mardin; Sutter' s Mill; Chisholm Trail; Dolby Brothers Drovers and Livestock; Chase County; trails